Occult hepatitis C virus infection in Iranian hemodialysis patients - Ali Eslamifar; Amitis Ramezani; Hassan Ehteram; Effat Razeghi; Farrokhlagha Ahmadi; Manouchehr Amini; Mohammad Banifazl; Gelavizh Etemadi; Hossein Keyvani; Anahita Bavand; Arezoo Aghakhani (Society of Diabetic Nephropathy Prevention, 2015)
Background: Occult hepatitis C virus (HCV) infection is defined as the presence of HCV-RNA in liver or peripheral blood mononuclear cells (PBMCs) in the absence of detectable hepatitis C antibody (anti-HCV) or HCV-RNA in the serum. Low concentrations of HCV-RNA may be detected in PBMCs of hemodialysis (HD) patients and this could have a great impact on the management of HD patients. Objectives: The aim of this study was to detect the occult HCV infection in Iranian HD patients. Patients and Methods: A total of 70 anti-HCV negative HD patients from three dialysis units in Tehran, Iran were included in this study. In these cases, presence of HCV-RNA in plasma samples was tested by reverse transcriptase-nested polymerase chain reaction (RT-nested PCR). In cases with negative anti-HCV and plasma HCV-RNA, genomic HCV-RNA was checked in PBMC specimens by RT-nested PCR. Results: Seventy anti-HCV negative HD patients were enrolled in the study. 32.85% and 1.43% of cases had elevated levels of alanine aminotransferase (ALT) and aspartate aminotransferase (AST) respectively. 7.14% of patients had elevated levels of both ALT and AST. HCV-RNA was negative in plasma samples of all anti-HCV negative HD subjects. The genomic HCV-RNA was not detected in any PBMC samples of HD cases with negative anti-HCV and plasma HCV-RNA. Conclusions: Occult HCV infection was not detected in our HD patients despite of elevated levels of liver enzymes in some participants. Further studies involving larger number of HD patients are required to elucidate the rate of occult HCV infection in HD cases.